(untitled) (Research, Society and Development, 2020)
Educational, social and economic changes bring the teacher the mission of choosing teaching strategies for academics of different generations, as well as the choice of methods that reach higher levels of cognitive domains. Thus, this study aims to understand the relationship between the teaching strategies chosen, participation in study groups, and learning in higher education academics, through a reflective approach to literature. It was, therefore, an integrative literature review, with a reflexive approach in which the sample was composed of articles published in national and international journals written in English, Spanish and Portuguese, without distinction of year since they addressed in their development the study group influences for academics, learning strategies and teaching methods. As a result, it was observed that the use of new teaching methods in favor of more efficient learning has been generating a positive effect on student education. Just as active participation in the study group allows it to identify the points of difficulty in absorbing the content. Through the activities proposed by the team, it also seeks different strategies to enhance this learning, with greater motivation to learn and participate in classes, avoiding the accumulation of content. However, the need for a constant search for improvement of educational means is emphasized, which forces the teacher, or even the institution that leads it, to search for strategies that best suit the profile of each course or even each student.